Algebraic Coding Theory Using Pell Equation x2 − 8y2 = 1 - Janaki, G; Gowri, Shankari A (Ratio mathematica, 2023)
An interdisciplinary field with significant practical use is cryptography. The difficulty of specific mathematical computing tasks affects a public key cryptosystem’s security. The technique for coding and decoding the messages was described in this work, utilising the solutions of Pell equation x2 - 8y2 = 1 and matrix Q8∗. It was noted that messages can be turned into an even size that is then divided into slabs.